Loss Aversion and Lying Behavior: Theory, Estimation and Empirical Evidence - Ellen Garbarino; Robert Slonim; Marie Claire Villeval (Institute for the Study of Labor (IZA), 2016)
We theoretically show that agents with loss-averse preferences facing a decision to receive a bad financial payoff if they report honestly or to receive a better financial payoff if they report dishonestly are more likely to lie to avoid receiving the low payoff the lower the ex-ante probability of the bad outcome. This occurs due to the ex-ante expected payoff increasing as the bad outcome becomes less likely, and hence the greater the loss that can be avoided by lying. We demonstrate robust support for this role of loss aversion on lying by reanalyzing the results from the extant literature covering 74 studies and 363 treatments, and from two new experiments that vary the outcome probabilities and examine lying for personal gain and for gains to causes one supports or opposes. To measure and compare lying behavior across treatments and studies, we develop an empirical method that estimates the full distribution of dishonesty when agents privately observe the outcome of a random process and can misreport what they observed.
Keywords: C91; C81; D03; 330; econometric estimation; dishonesty; loss aversion; experimental economics; lying